Unveiling the Toxin Genes of Vibrio cholerae in Seafood: A Collaboration of Phenotypic and Genotypic Approaches - Ni Luh Budi Artaningsih; I Putu Bayu Mayura; Ni Nyoman Sri Budayanti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Vibrio cholerae is a pathogenic bacterium that causes cholera, a severe diarrheal disease transmitted through contaminated food or water, particularly seafood such as fish, shrimp, and shellfish. This review aims to provide a comprehensive overview of studies that have identified and characterized toxin genes of V. cholerae in seafood using phenotypic and genotypic approaches. The literature review was conducted using online databases including PubMed, ScienceDirect, Scopus, Web of Science, and Google Scholar with keywords “Vibrio cholerae”, “virulence gene”, “cholera toxin”, “phenotypic-genotypic detection”, “cholera infection”. Selected articles were published between 2015 and 2025 in English or Indonesian and discussed the identification of V. cholerae toxin genes from marine products. The findings revealed that V. cholerae isolates from seafood commonly harbor virulence genes such as ctxA, hlyA, ompW, tcpA, zot, ace, and rtx, which play crucial roles in colonization, toxin production, and pathogenicity. Phenotypic detection using TCBS agar and hemolysis tests serves as an initial screening, whereas genotypic identification through PCR and sequencing offers higher sensitivity and specificity. Combining both methods enhances detection accuracy and risk assessment. Therefore, monitoring virulence genes of V. cholerae in seafood is essential for strengthening food safety surveillance and preventing cholera outbreaks in coastal and tourism areas